The Influence of Self-Control and Materialism on Online Impulsive Buying on the Shopee Application in Gianyar Regency, Bali - Putu Tito Suardharma Putra; Ni Putu Yuliana Ria Sawitri; I Gusti Putu Agung Widya Goca (Countable (Contemporary Business and Sustainability Science), 2025)
Online impulse buying has become an increasingly rampant phenomenon in consumer behavior, including in Gianyar Regency, Bali. This research aims to explore the influence of self-control and materialism on online impulse buying on the Shopee application in Gianyar Regency, Bali. The research method used was descriptive quantitative, with a research sample of 110 people in Gianyar Regency, Bali taken using purposive random sampling. The results of the partial hypothesis testing analysis of the influence of self-control and materialism on online impulsive buying through the t-test were proven to have a positive and significant effect. Simultaneous testing has the results of a positive and significant effect on online impulsive buying on the Shopee application in Gianyar Regency, Bali. This research can help develop more effective marketing strategies and design more appropriate policies to reduce online impulse buying in the Gianyar Regency area, as well as provide a strong basis for further research in this area.